SUPERVISI PENDIDIKAN SEBAGAI ALAT MEMPERKUAT POSISI PEREMPUAN DALAM PENDIDIKAN - Arini Dwi Cahyani (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
Women do not get the same opportunities for promotion and career development as their male counterparts. This research aims to explore how educational supervision can be used strategically to strengthen women's position in education. This research uses a descriptive qualitative research approach. The research was conducted at the Community Learning Activity Center (PKBM) in As-Salam, Pasuruan Regency. The research period is 3 months, namely March-May 2024. The research subjects are female educators/teachers and the head of PKBM As-Salam Pasuruan Regency. Data collection techniques, namely in-depth interviews, participant observation, and documentation. The research results show that educational supervision provides emotional support, increases competence, and expands career opportunities for female teachers. Developing inclusive practices, providing moral support, and reducing gender inequality are the main findings in this research. The implication of this research is the importance of strengthening the role of educational supervision in supporting the welfare and empowerment of female teachers in education. The implication of this research is the importance of strengthening educational supervision in supporting women's empowerment in equal education, as well as creating an inclusive and fair learning environment for all individuals. The results of this research can provide a valuable contribution to the development of more inclusive and equitable educational policies and practices.